1999
DOI: 10.1007/s004290050278
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase-containing projections to the ventrobasal thalamus in the rat

Abstract: Microiontophoretic studies of thalamic neurons suggests that nitric oxide (NO) plays an important role in mediating somatosensory transmission. The thalamus contains few nitric oxide synthase (NOS)-immunoreactive neurons; thus, the major source of thalamic NO is presumably from NOS-positive axons of extrathalamic origin. The cells of origin of these putative NOS-containing pathways to the ventrobasal thalamus were investigated in rats by combining retrograde tracing with immunocytochemistry for NOS. The locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 111 publications
2
24
1
Order By: Relevance
“…An ipsilateral spinothalamic tract was reported in the rat (Burstein et al 1990;Usunoff et al 1999), and clinical observations indicate that ipsilaterally projecting spinothalamic neurons exist also in humans (reviewed by Nathan et al 2001). In the rat, the ipsilateral spinothalamic projection is significant: according to Burstein et al (1990), the ipsilaterally projecting cells are approximately 10% of the total spinothalamic neuronal population.…”
Section: Discussionmentioning
confidence: 99%
“…An ipsilateral spinothalamic tract was reported in the rat (Burstein et al 1990;Usunoff et al 1999), and clinical observations indicate that ipsilaterally projecting spinothalamic neurons exist also in humans (reviewed by Nathan et al 2001). In the rat, the ipsilateral spinothalamic projection is significant: according to Burstein et al (1990), the ipsilaterally projecting cells are approximately 10% of the total spinothalamic neuronal population.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have, however, addressed the coexistence of NOS and Ach within the brainstem parabrachial region. Usunoff et al (1999) reported that ϳ25% of rat LDT/pedunculopontine tegmental (PPN) projection neurons which target VB stain positively for NADPHd. A similar percentage of parabrachial (LDT/PPN) neurons was found to also co-contain Ach and project to the dorsal lateral geniculate nucleus in feline (Bickford et al, 1993).…”
Section: Differential Expression Of Nos and 5ht In Subcortical Dr Promentioning
confidence: 99%
“…16 and 19). In VP and the somatosensory part of the RTN, the number of similar terminals originating from brainstem fibers is extremely small, and they use transmitters other than glutamate (20,21).…”
Section: Differences In Number Of Glur4 Subunits At Corticothalamic Smentioning
confidence: 99%